2015
DOI: 10.1080/08870446.2015.1062482
|View full text |Cite
|
Sign up to set email alerts
|

Understanding adolescent type 1 diabetes self-management as an adaptive process: A grounded theory approach

Abstract: This investigation provides a conceptual understanding of the complex issues adolescents encounter while adapting to and integrating a diabetes self-management regime into their lives. It provides an invaluable framework for exploring psychological mechanisms and contextualising them within a self-management continuum. Implications for healthcare professionals are discussed and further research proposes whether the model could be applicable to other chronic illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…Analysis of the data coded under 'coping with LTCs' revealed a striking finding: the heterogeneity of coping resources that could be utilised both within and across individual participants. Ability to cope with LTCs did not seem to follow a linear trajectory that the literature on adaptation to illness suggests (Chilton and Pires-Yfantouda 2015). Rather, people living with LTCs could exhibit sophisticated strategies for self-management and adjusting one's life in response to illness (classified as high-level coping), while simultaneously referring to a high emotional burden of illness and/or behaviours such as comfort eating or substance abuse (classified as low-level coping).…”
Section: Resultsmentioning
confidence: 95%
“…Analysis of the data coded under 'coping with LTCs' revealed a striking finding: the heterogeneity of coping resources that could be utilised both within and across individual participants. Ability to cope with LTCs did not seem to follow a linear trajectory that the literature on adaptation to illness suggests (Chilton and Pires-Yfantouda 2015). Rather, people living with LTCs could exhibit sophisticated strategies for self-management and adjusting one's life in response to illness (classified as high-level coping), while simultaneously referring to a high emotional burden of illness and/or behaviours such as comfort eating or substance abuse (classified as low-level coping).…”
Section: Resultsmentioning
confidence: 95%
“…In some studies, the process of children assuming self‐management responsibility was viewed by children and parents as part of normal development but often described as a complex, uneven process (Chilton & Pires‐Yfantouda, ; Karlsson, Arman, & Wikblad, ). Roles and responsibilities of children and their parents changed over time (Christian, D'Auria, & Fox, ; Olinder et al, ) as children became less reliant on their parents and parents “let go” (Babler & Strickland, ; Ersig, Tsalikian, Coffey, & Williams, ).…”
Section: Resultsmentioning
confidence: 99%
“…Some aspects of self‐management were taken on gradually by children, including managing medication, therapies, and procedures (Buford, ; Meaux et al, ; Williams, Mukhopadhyay, Dowell, & Coyle, ), whereas skills such as decision making and liaising with services needed to be acquired suddenly on transfer to adult services (Kirk, ). The parent‐to‐child transfer of self‐management responsibility was modelled in various ways; some studies reported that the child, the parent or both, sequentially progressed through discrete stages (Babler & Strickland, ; Schilling, Knafl, & Grey, ) whereas others viewed the transfer as a fluid, bidirectional continuum where child and parental roles and responsibilities were regularly shifting (Chilton & Pires‐Yfantouda, ; Williams et al, ). For example, in some families, parents would resume management of the LTC when their child was tired, unwell, or lacking motivation (Kirk, ; Schilling et al, ) or when complications arose (Meaux et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The teenagers and parents in the study particularly valued the closed-loop as it was seen to offer a safety net at a point in the life course where the self management of diabetes could be neglected as a result of individuals having other priorities and wanting to fit in with their peers [26,27]. Indeed, the particular benefits of closed-loop technology to this age group have been noted by others, who have shown that in scenarios mimicking 'noncompliant' behaviours among adolescents, closed-loop systems can be safe and effective because of the system's ability to partly compensate for boluses being forgotten or underestimated [28,29].…”
Section: Discussionmentioning
confidence: 99%